ANALISIS RASIO KEUANGAN DAN NON KEUANGAN UNTUK MEMPREDIKSI FINANCIAL DISTRESS - Inesya Epriliana; Suwandi Suwandi (PROCEEDING UMSURABAYA, 2022)
ABSTRACTThis study aims to analyze the effect of financial and non-financial ratios to predict financial distress. The financial ratios used in this study include CAMEL: Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Net Interest Margin (NIM), Return On Assets (ROA), Operating Costs and Operating Income (BOPO) and Loan To Deposit Ratio (LDR). While non-financial used in this study include the exchange rate and inflation. Financial distress as the dependent variable can be measured using the Modified Altman Z-Score formula. The population used in this study are conventional banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period with 152 data. Determination of the sample is done by using purposive sampling technique. The data analysis technique used is multiple linear regression analysis. The results showed that the Capital Adequacy Ratio (CAR), Operating Costs and Operating Income (BOPO) and Loan To Deposit Ratio (LDR) had a significant effect on financial distress. Meanwhile, Non-Performing Loans (NPL), Net Interest Margin (NIM), Return On Assets (ROA), exchange rates and inflation have no effect on financial distress.Keyword :  CAMEL; Financial Distress; Inflation; Exchange Rate ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh rasio keuangan dan non keuangan untuk memprediksi financial distress. Rasio keuangan yang digunakan dalam penelitian ini meliputi CAMEL:Capital Adequacy Ratio (CAR), Non Perfoming Loan (NPL), Net Interest Margin (NIM), Return On Assets (ROA), Biaya Operasional Dan Pendapatan Operasional (BOPO) dan Loan To Deposit Ratio (LDR). Sedangkan non keuangan yang digunakan dalam penelitian ini meliputi kurs dan inflasi. Financial distress sebagai variabel dependen yang dapat diukur menggunakan rumus Altman Z-Score Modifikasi. Populasi yang digunakan dalam penelitian ini adalah perusahaan perbankan konvensional yang terdaftar di Bursa Efek Indonesia (BEI) periode 2017-2020 sebanyak 152 data. Penentuan sampel dilakukan dengan menggunakan teknik purposive sampling. Teknik analisis data yang digunakan yakni analisis regresi linier berganda. Hasil penelitian menunjukkan bahwa Capital Adequacy Ratio (CAR), Biaya Operasional Dan Pendapatan Operasional (BOPO) dan Loan To Deposit Ratio (LDR) berpengaruh signifikan terhadap financial distress. Sedangkan Non Perfoming Loan (NPL), Net Interest Margin (NIM), Return On Assets (ROA), kurs dan inflasi tidak berpengaruh terhadap financial distres. Kata Kunci      : CAMEL; Financial Distress; Inflasi; Kurs